2004
DOI: 10.1159/000077034
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Myosin Heavy Chain Isoforms in Different Fibre Types of Canine Trunk and Limb Skeletal Muscles

Abstract: The aim of this study was to determine the pattern of myosin heavy chain (MHC) isoform expressions within the muscle fibres of functionally diverse trunk and limb dog muscles using monoclonal antibodies that are specific to MHC isoforms. We found that three MHC isoforms are expressed in dog skeletal muscles. The pattern of their expressions determined the existence of ‘pure’ fibres, i.e. I and IIa, both expressing only one MHC isoform, and ‘hybrid’ fibres, i.e. I/IIa and IIa/x, that co-expressed two MHC isofor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
33
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 68 publications
(47 reference statements)
5
33
0
Order By: Relevance
“…However, in the muscles that contained only a weak MHC-IIx band ( fi g. 1 e), no type IIX fi bres could be demonstrated immunohistochemically. Since BF-35 recognizes MHC-IIa, only pure IIX and hybrid IIAX fi bres with the predominant MHC-IIx isoform can be demonstrated with this antibody [Smerdu and Eržen, 2001;Štrbenc et al, 2004]. It implies that in these muscles, the MHC-IIx isoform was obviously co-expressed with MHC-IIa in type IIA fi bres (or more precisely type IIAX fi bres), but its content was too low to be detected by BF-35.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the muscles that contained only a weak MHC-IIx band ( fi g. 1 e), no type IIX fi bres could be demonstrated immunohistochemically. Since BF-35 recognizes MHC-IIa, only pure IIX and hybrid IIAX fi bres with the predominant MHC-IIx isoform can be demonstrated with this antibody [Smerdu and Eržen, 2001;Štrbenc et al, 2004]. It implies that in these muscles, the MHC-IIx isoform was obviously co-expressed with MHC-IIa in type IIA fi bres (or more precisely type IIAX fi bres), but its content was too low to be detected by BF-35.…”
Section: Discussionmentioning
confidence: 99%
“…Type IIX fibers are histochemically very similar to Type IIB fibers and MHC IIx has been shown to be expressed in fibers histochemically identified as Type IIB, but both types differ in their contractile properties (Pette et al, 1999;Smerdu et al, 2009). In contrast to small mammals, results on larger species have shown that only MHC IIa and IIx were expressed but not MHC IIb (e.g., cat: Talmadge et al, 1996;dog: Snow et al, 1982;Š trbenc et al, 2004;goat: Argü ello et al, 2001;sheep: Maier et al, 1992;human: Smerdu et al, 1994;Ennion et al, 1995;horse: Rivero et al, 1996;Eizema et al, 2003;cattle: Tanabe et al, 1998;brown bear: Smerdu et al, 2009). However, Type IIB and IIX fibers are not distinguishable with the Ziegan protocol used in this study.…”
Section: Histochemistrymentioning
confidence: 99%
“…muscles from adult animals and muscles that have not been subjected to 'transforming conditions', such as changes in the neural impulse pattern or hormone levels [Stephenson, 2001]. For instance, it was found that hybrid fibers were common among fast fibers expressing MyHC-IIX [Strbenc et al, 2004]. Muscle fibers have a length of a few millimeters to several centimeters.…”
Section: Introductionmentioning
confidence: 99%